Pseudocromata, a new genus of Ochlerini based on a new species from Ecuador (Pentatomidae: Discocephalinae) - Ortega-León, Guillermina; Thomas, Donald B. (Zootaxa, 2016)
The tribe Ochlerini was defined by Rolston (1981) based on the position of abdominal trichobothria (lateral to the spiracles), insertion of the labium well behind the apex of the head (usually in line with the eyes), and the superior surface of the distal metatarsomere in females excavate or flattened. Rolston’s (1992) revision of the tribe included 28 genera. With subsequent additions there are now either 33 or 35 genera depending on the inclusion or exclusion of Melambyrsus Breddin (listed as nomen dubium by Rolston 1992) and Candeocoris Roell & Campos (2015) which has character-states intermediate between Ochlerini and Discocephalini. With few exceptions the members of the tribe are inornately colored, typically shades of black, brown or tan Campos & Grazia (2006). Exceptions are species in the genera Cromata Rolston and the aforementioned Candeocoris which have colorful blotches on the scutellum and corium.